Testing the internal/external frame of reference model of academic achievement and academic self-concept with open self-concept reports. (June 2018) - Wolff, Fabian; Nagy, Nicole; Helm, Friederike; Möller, Jens
Abstract: The internal/external frame of reference model (I/E model) describes the relations between math and verbal achievement and self-concept. Whereas math and verbal achievement are positively associated with the corresponding self-concept, they are negatively associated with the non-corresponding self-concept. As yet, investigations of the I/E model have concentrated on quantitative self-concept assessments in closed-ended questionnaires. The present study aims to investigate whether the patterns of the I/E model are replicated when open-ended self-concept measures are used. Assessing open as well as closed self-concepts of N = 471 German high school students provides evidence for the generalizability of the I/E model to open-ended self-concept assessments: We found the typical I/E model patterns with both open and closed self-concepts. Highlights: The I/E model-like relations might be biased by close-ended self-concept measures. Yet, the I/E model-like relations also hold for open-ended self-concept measures. Thus, the I/E model can be generalized across different assessment methods. Social and dimensional comparisons affect broad domain-specific self-views. The I/E model is not just an artefact of the close-ended assessment method.